GEL PERMEATION CHROMATOGRAPHY FOR FRACTIONATION AND ISOTOPE RATIO ANALYSIS OF STERANES AND TRITERPANES IN OILS - Inaba T.; Suzuki N. (My University, 2003)
Gel permeation chromatography (GPC) was applied to concentrate steranes and triterpanes in oils and measure their compound-specific carbon isotope ratios (δ13C). Trace steranes and triterpanes were concentrated from n-alkane-rich Miocene Yabase marine oils by GPC. δ13C was determined by gas chromatography-combustion/isotope ratio-mass spectrometry (GC-C/IR-MS). The δ13C of cholestane from the Yabase oil ranges from -24.4 to -26.3%%. This is nearly consistent with that of the n-C18 to n-C20 alkanes, suggesting significant algal and zooplankton contribution. The δ13C of ethylcholestane from the Yabase oil is comparatively light, ranging from -26.7 to -30.8%%. It is similar to the δ13C of n-C27, n-C29, n-C31 alkanes and oleanane, suggesting a significant contribution of terrestrial higher plant material.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен